Application of a simple measuring method to evaluate the fecal microflora of dairy cows in the summer season - Amimoto, Miki; Ouchi, Yoshimitsu; Okita, Miki; Hirota, Takashi; Imura, Yoshimi; Bungo, Takashi (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: The effect of seasonality needs to be considered in designing future studies because global warming has caused a rise in ambient temperatures. The objective of the present study is to investigate the effect of high ambient temperatures on fecal score and fecal microflora in dairy cows during summer. Materials and Methods: During the 7 days before the sampling of feces, the daily mean temperatures were 19.9°C in early summer and more than 27.5°C in late summer. Fecal samples were collected from the rectum of cows and the fecal score was evaluated on a 4-point scale. The equalized samples were used to extract the genomic deoxyribonucleic acid (DNA) of the bacteria (Escherichia coli, Salmonella, Lactobacillus, and Bifidobacterium). Results: There was no significant difference in fecal scores between the sampling times in early and late summer. In the populations of the bacteria, there was no significant difference between sampling days in the DNA level of Salmonella, and E. coli in late summer increased to more than three times the level in early summer. However, both levels of Lactobacillus and Bifidobacterium in early summer significantly decreased after 2 months. Conclusion: These data suggest that the increase in temperature in late summer may adversely affect the populations of bacteria in the intestinal environment of dairy cows. In addition, the method used in the present study was sufficient to evaluate the changes in internal and external environmental conditions of dairy cattle. J. Adv. Vet. Anim. Res., 8(2): 307-311, June 2021